Assessing Human Resource Management Practices in District Assemblies in the Ashanti Region - Wiafe Owusu, James (2015)
thesis submitted to the Department of Managerial Science, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the degree of MASTERS OF BUSINESS ADMINISTRATION (HUMAN RESOURCE MANAGEMENT OPTION).